2010
DOI: 10.2489/jswc.65.5.304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of outreach on the awareness and adoption of conservation practices by farmers in two agricultural watersheds of the Mackinaw River, Illinois

Abstract: Increased awareness of the contributions of nonpoint source runoff to the degradation of water quality in the Mississippi River and Gulf of Mexico emphasizes the need to increase conservation practices that reduce nutrient export from agricultural lands. To achieve long-term conservation goals in agricultural landscapes, it is important to understand farmers' perspectives on what practices are effective, practical, and economically attainable. We conducted a series of surveys, interspersed with focused outreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Outreach is essential to successfully increasing BMP implementation within large agricultural landscapes and targeting BMP placement to landscape areas with the highest contributions to water quality impairments and where BMPs will be most effective (Walter et al, 2007; Lemke et al, 2010). Even with 95% of the stream length protected by buffers, our results showed consistently higher export of TSS in the treatment watershed than in the reference watershed.…”
Section: Discussionmentioning
confidence: 99%
“…Outreach is essential to successfully increasing BMP implementation within large agricultural landscapes and targeting BMP placement to landscape areas with the highest contributions to water quality impairments and where BMPs will be most effective (Walter et al, 2007; Lemke et al, 2010). Even with 95% of the stream length protected by buffers, our results showed consistently higher export of TSS in the treatment watershed than in the reference watershed.…”
Section: Discussionmentioning
confidence: 99%
“…He found that conservation education training is the primary tool available to effect practice change. Extension services provide timely and effective information on practices as well as new technologies [76,88,101,102], and proximity to extension agents increases adoption [101]. Atwell et al [47], Kalcic et al [104] and Woods et al [62] found that interactions with local conservation staff frequently are positively correlated with adoption.…”
Section: Information and Awareness Of Bmpsmentioning
confidence: 99%
“…Water quality initiatives are often hampered by limited farmer participation which has in turn been shown to be hindered by limited outreach capacity and inflexible policy (Lemke et al 2010, Jordan et al 2011. Facilitating broader farmer participation requires understanding of comprehensive farmer perspectives in order to 'calibrate' appropriate and effective programming.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Garbach et al (2012) found that silvopastoral conservation practices providing significant private benefits (primarily increased agricultural productivity) were adopted more readily than practices perceived to provide relatively greater public benefits, the latter of which had adoption rates benefiting from implementation of positive incentive payments. Cost-share and technical support (especially when provided in such a way to not conflict with timing of field operations) combined with International Journal of Agricultural Sustainability intensive outreach efforts was an effective mechanism for encouraging adoption of conservation practices in an Illinois watershed (Lemke et al 2010). Reimer et al's (2012) qualitative study concluded non-monetary incentives such as highlighting of off-farm benefits and the concept of community-based stewardship as a motivator could be used for the promotion of practices providing environmental (public) benefits beyond economic (private).…”
mentioning
confidence: 99%